Reverse discussion statement retrieval method and equipment based on BERT model - SHI HONGGUANG; RUAN JINXIU (2023)
The invention discloses a BERT model-based reverse argument statement retrieval method and equipment, and the method comprises the steps: constructing a formal data set which is a contextual statement corresponding to an argument statement, and marking whether a second argument statement is a reverse argument statement of a first argument statement or not by yi; a Bipolar-encoder model is proposed on the basis of a pre-training model, joint training is used for measuring whether context statements are associated or not, whether two discussion statements are mutually reversed or not is measured, and if the two discussion statements are mutually reversed, the two discussion statements should have the same subject but have different sites. According to the method, the topic similarity and the vertical dissimilarity are considered at the same time under the condition that no topic priori information exists, the gradual time complexity is low during retrieval, and good effects and performance can be continuously k